Association of high-sensitivity C-reactive protein with hepatic fibrosis in patients with metabolic dysfunction-associated steatotic liver disease - Wu, Yunfei; Zheng, Guojun; Zhang, Fan; Li, Wenjian (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the association between high-sensitivity C-reactive protein (hsCRP) levels and hepatic fibrosis in patients with metabolic dysfunction-associated steatotic liver disease (MASLD) and assess its predictive efficacy.MethodsThe study included 1,477 participants from the United States and 1,531 from China diagnosed with MASLD. Liver stiffness measurement (LSM) and controlled attenuation parameter (CAP) were assessed by vibration-controlled transient elastography (VCTE) to evaluate the presence and degree of hepatic fibrosis and steatosis. The relationship between hsCRP levels and hepatic fibrosis in MASLD patients was examined using multivariable-adjusted and restricted cubic spline (RCS) models. Additionally, subgroup analyses were conducted to investigate the potential heterogeneity among different characteristic subgroups.ResultsThe results demonstrated a significant correlation between elevated hsCRP levels and an increased risk of significant fibrosis, advanced fibrosis, and cirrhosis in the US cohort of MASLD patients (OR 2.22, 1.69, and 2.85, respectively; all P <0.05). The results of the Chinese cohort were consistent with those of the US cohort, and there was a significant and positive correlation between hsCRP levels and the risk of hepatic fibrosis in patients with MASLD (OR 2.53, 3.85, and 3.78, respectively, all P <0.001). The RCS analysis revealed a significant non-linear relationship between hsCRP levels and the degree of hepatic fibrosis, with disparate inflection point values observed across different cohorts (approximately 9 mg/L in the US cohort and 4 mg/L in the Chinese cohort). The impact of hsCRP levels on the risk of hepatic fibrosis varied across different subgroups with distinct characteristics.ConclusionThe present study demonstrated a significant correlation between hsCRP levels and the degree of hepatic fibrosis in patients with MASLD, with notable dose-response relationships and subgroup differences.